Pragmatism, Practice, and the Boundaries of Organization - Whitford, Josh; Zirpoli, Francesco (Organization Science, 2014)
This article uses a longitudinal qualitative analysis of key transitions in the relationship between Fiat Group Automobiles and a major supplier to integrate a pragmatist model of action into the contemporary “practice” approach to the study of organizations. It builds on an affinity between pragmatist and practice approaches that has been widely recognized but has not yet been fully developed with reference to an empirical case. It argues that an analytic reliance on a pragmatist conception of agency improves on the more general reliance in studies of organizational practice on a conception of the agent imported from Giddens’ structuration theory [Giddens A (1984) The Constitution of Society: Outline of the Theory of Structuration (Polity Press, Cambridge, UK)]. The argument is developed with reference to a long-standing debate in organization theory—the debate over the determinants of organizational boundaries—that has grown in importance as companies have responded to market and technological volatility by involving suppliers not just in the production but also in the conceptualization and design of the products they sell. It provides a theoretical framework that can help analyze the place of managerial agency in organizational strategy making and explain why organizational boundaries in many industries today are so unsettled and contested and are likely to remain so in the future.